PENGUATAN MODAL SOSIAL DALAM PENANGANAN PRODUK OLAHAN KOPI PADA KOMUNITAS PETANI KOPI DI KABUPATEN JEMBER - Rokhani Said (University of Jember, 2012)
Study of social capital in coffee farmer community to diversify product has not been done. This study aimed: (1) to describe the conditions of social capital in farmer community who diversify coffee products, (2) to map the components of social capital which are still strong and which still need strengthening, (3) to formulate development strategies of product diversification on coffee products. The location of study is determined purposively in 5 (five) village in five sub districts in Jember District: Sidomulyo in Silo Sub District, Sucopangepok in Jelbuk Sub District, Rowosari in Sumberjambe Sub District, Sumbersalak in Ledokombo Sub District and Kemiri in Panti Sub District. The data were analyzed using descriptive method. The results of this study are: the strong element of social capital are: partnership, trust, norm, custom and local culture value, tolerance, local wisdom and knowledge, social leadership, community participation, independence, freedom of mobility , the ability to buy